The Practicality of Popular Ethnobotany Scientific Books on Mangrove Plants Genus Avicennia, Tabanio Village - Ayatul Fajrin; Dharmono Dharmono; Muhammad Zaini (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Learning using popular scientific books based on the local potential of an area is one solution that can be used to overcome problems that often arise such as a lack of student reading interest due to boring teaching materials and learning media in Ethnobotany courses, especially in some ethnobotany studies that require students to interact directly with the community. This development research aims to describe the practicality of a popular scientific book prototype entitled